Impact of Drug Interaction on Time in Therapeutic Range of Patients Receiving Oral Anticoagulation Therapy - M, Ramya; Suresh, Nitya; Jose, Josna (Indian Journal of Pharmacy Practice)
Objectives: Drug-drug interactions (DDIs) are a significant consideration in Anticoagulation management. The objective of this study was to identify DDIs with Vitamin K Antagonists (VKAs) and to assess the effect of DDIs on Time in Therapeutic range (TTR) (percentage of time a patient’s INR is within the desired treatment range). Methods: An Observational study carried over a period of 6 months. Patients taking VKAs are included in this study. Patient data were collected from patient records and hospital information system. TTR calculation was done using the Rosendaal method. Drug interaction was checked using the Drug interaction checker (Micromedex) and online Lexi Interact. Criticality index was calculated using “Failure Modes, Effects and Criticality Analysis” (FMECA) method. Association between DDIs and TTR were assessed. Results: Fifty four DDIs were identified in a total of 150 patients (mean age 55.47 years, 56.66% women). Twenty one drugs were potentially interacting with VKAs. Four drugs have a criticality index of ≥10 are considered as high risk for interacting with VKAs. The mean TTR was 33.12±26.06%, 20 patients (13.33%) were under good control and 130 patients (86.67%) were under poor control. Out of fifty four DDIs, Fifty one DDIs (94%) are in poor control population. Drug interaction and clinical events such as bleeding and thromboembolism were significantly associated (p=0.01). Drug interaction (p=0.02) was a significant predictor of poor control of TTR. Conclusion: DDI is one of the major factors that alter the percentage number of days the patients were in the desired INR range (TTR).
Keywords: Vitamin K Antagonist; Drug interaction; Clinical events; Criticality index; Time in Therapeutic Range.